Pengaruh Pemberian Tablet Tambah Darah untuk Mencegah Anemia Terhadap Pengetahuan Remaja Putri di SMK Dharma Patra Pangkalan Susu Tahun 2024 - Gultom, Yohana Tetty; Beringin Jaya Munthe (Universitas Methodist Indonesia, 2025)
The increased nutritional requirements of adolescent girls are associated with rapid physical growth and development, along with lifestyle changes and eating behaviors that influence nutrient intake. Adolescence is a critical period that is highly susceptible to nutritional problems, particularly anemia. Data from Riskesdas 2018 indicate that the prevalence of anemia among adolescent girls in Indonesia reached 48.9%. This study sought to evaluate the effect of counseling disseminated via leaflet media on the knowledge of adolescent girls concerning blood supplement tablets at SMK Dharma Patra, Pangkalan Susu District, in 2024. The study employed a pre-experimental design using a one-group pretest–posttest approach, involving 79 female students in grade ten selected through stratified random sampling. Data analysis was performed using the Wilcoxon test. The findings showed an increase in the average knowledge score from 54.05 (SD 8.810) prior to counseling to 87.59 (SD 7.065) after counseling, with a mean improvement of 33.54 points. The statistical test yielded a p-value of 0.000 (<0.05), indicating that leaflet-based counseling had a significant effect on enhancing adolescent girls’ knowledge for anemia prevention. Therefore, the use of leaflet media is recommended for schools and local health centers as an effective tool in nutrition education programs.